Differences in Immune Response between HCV Positive, HIV Negative Haemophilia A and B Patients - Meijer, K.; Smid, W. M.; Verspiek, S. P. J.; Smit, J. W.; van der Meer, J. (Thrombosis and Haemostasis, 1998)
We measured numbers of lymphocytes and subsets in seven HIV negative, HCV positive severe haemophilia B patients, before and after substitution was changed from prothrombin complex concentrate to monoclonally purified concentrate. Data were compared with controls and our previous findings in haemophilia A.At baseline, haemophilia B patients did not differ from controls. After two years, T helper cells showed an increase (p = 0.028), while a rise in B cells approached statistical significance (p = 0.063). Haemophilia A patients showed increased numbers of activated non-B lymphocytes (p = 0.003) and lowered numbers of B cells (p = 0.001) at baseline. After two years activated non-B lymphocytes decreased (p = 0.004), as did the CD4/CD8 ratio (p = 0.002), due to increasing numbers of CD8 positive cells (p = 0.087).Our data suggest minor inhibition of the immune system in haemophilia B patients, which recovers after changing therapy to a monoclonally purified product. These findings contrast with the excessive immune stimulation in haemophilia A. The observed differences might be due to the administered concentrates.